Princess Evie's ponies : Sprinkles the magic cupcake pony - Kilbride Sarah; Tilley, Sophie (London : Simon and Schuster, 2013)
In this adventure, neptune the Magic Sea Pony takes Princess Evie to a sparky undersea world whre a mermaid has lost her precious pink pearl.
Keywords: Mermaids -- Fiction; Ponies -- Fiction; Princesses -- Fiction